WhatsApp-Mediated Language Teachers’ Reflection of Classroom Practice: Experience of Indonesian Context - Prayogo, Agus; Widyaningrum, Lulut (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This qualitative case study examines language teachers’ reflective practice mediated by WhatsApp application and addresses the topics mostly reflected in the eight topics of classroom practice and the problems faced. A total of 537 entries of chats written, the most common topic of reflection entries is about general teaching approaches. Time restraint and writing chats in English become significant problems of the reflective practice. The practice has provided an online environment that lets teachers interact and share with colleagues to construct knowledge and evaluate teaching practice that beneficial for teacher professional development. Teachers have gained benefits from online reflection collaboration with other teachers, but most of them take into account the need for an online reflection setting that gives freedom to use the language that they are comforted with